Insecticides Basic and Other Applications - Soloneski, Sonia; Larramendy, Marcelo (IntechOpen, 2012)
It is our hope that this book will be of interest and use not only to scientists, but also to the food-producing industry, governments, politicians and consumers as well. If we are able to stimulate this interest, albeit in a small way, we have achieved our goal.